The Effectiveness of Active Thinking Strategy in the Achievement of Fifth Grade Literary Students in the Subject of Philosophy and Psychology - Yaseen, Ali Tahseen; Al-Jubouri, Khamis Dhari (Journal of Tikrit University for Humanities, 2024)
This study investigates whether active thinking improves fifth-grade literary students’ philosophy and psychology grades. To fit the present investigation, the researcher used an experimental design with partial control and two equal groups, experimental and control. Division (B) was an experimental group whose students studied using the active thinking model, while Division (A) was a control group whose students studied normally. The research sample was (65) students after excluding the students who failed (32) and (33) in the experimental and control groups. Before getting started the experiment, the researcher made ensured the two study groups’ learners were statistically equivalent in many characteristics that can affect reliability. The researcher chose the first and second chapters of the book of philosophy and psychology for the fifth literary grade as the educational subject to teach, prepared behavioral goals within three levels, and created (16) model teaching plans for both groups.